Monitoring and Prediction of Ground Movements Above Underground Mines in the Eastern United States - M. Karmis (International Conference on Ground Control in Mining, 1987)
mining factors and representative ground movement parameters. Based on this analysis, the previously developed prediction methods were modified and tested for their applicability in the Appalachian coalfield. Finally, in order to facilitate the implementation of the prediction methods, as well as the data processing of the monitoring program, a number of computer software were developed and will be discussed in the paper. Surface deformations above underground mines and their prediction and control have been the topics of an extensive research effort by Virginia Polytechnic Institute and State University over the past few years. During the initial stages of this research, a number of case studies were collected from the literature, the mining industry and various government and state agencies and, based on the analysis of this information, appropriate prediction methods were proposed (Goodman, 1980; Webb, 1982; Hasenfus, 1984; Karmis et al., 1984). Although the prediction methods were based on sound concepts, it became evident that their accuracy and implementation were a reflection of the size and quality of the collected case studies. In this respect, the data bank was rather insufficient and posed certain questions regarding the development of subsidence information due to inappropriate length and spacing of monuments used in subsidence surveys, density and accuracy of such surveys, lack of monitoring horizontal movements, etc. In an effort to alleviate these problems, a comprehensive monitoring program was initiated in the coal mines of southwest Virginia, which included: - Two longwall and five room and pillar mines. - In total, seven longwall and sixteen room and pillar panels. - Monitoring lines in excess of 35,000 feet. - Vertical as well as horizontal measurements. A high accuracy digital computer tacheometer was used in all surveys and the type and spacing of all monuments were in accordance with well accepted guidelines. The data from this monitoring program completed the initially collected data bank and, thus, enabled a much needed statistical analysis between